Acceptability of lopinavir/r pellets (minitabs), tablets and syrups in HIV-infected children - Kekitiinwa, Adeodata.; Musiime, Victor.; Thomason, Margaret J.; Mirembe, Grace; Lallemant, Marc; Nakalanzi, Sarah.; Baptiste, David.; Walker, Sarah A.; Gibb, Diana M.; Judd, Ali (Europe PMC Funders Group, 2016)
Lopinavir/ritonavir ‘pellets’ were recently tentatively approved for licensing. We describe their acceptability for infants and children up to 48 weeks. Methods—CHAPAS-2 was a randomised, 2-period crossover trial comparing syrup and pellets in HIV-infected infants (n=19, group A, aged 3-<12 months) and children (n=26, group B, 1-<4yrs) and tablets and pellets in older children (n=32, group C, 4-<13yrs) from 2 clinics (“JCRC”, “PIDC”) in Uganda. At week 8, all groups chose which formulation to continue. Acceptability data were collected at weeks 0,4,8,12, and 48. Results—For groups A and B overall, the proportion preferring pellets increased between week 0 and week 12 and decreased at week 48 (group A 37%, 72%, 44%; group B 12%, 64% and 36% respectively), although there were marked differences between clinics. For group C, pellets were progressively less preferred to tablets over time: 41%,19%,13% at weeks 0,12,48 respectively. During follow-up unpleasant taste was similarly reported among young children taking pellets and syrups (37%/43% group A; 29%/26% group B), whereas among older children, pellets tasted worse than tablets (40%/2%). No participants reported problems with storage/transportation for pellets (0%/0%) unlike syrups (23%/13%). Conclusions—For children <4 years, pellets were more acceptable at week 12 but not week 48. Clinic differences could reflect bias among healthcare workers for different formulations. Pellets taste similar to syrup, are easier to store and transport than syrup, and represent an alternative formulation for young children unable to swallow tablets; improvements in taste and support for healthcare workers may help sustain acceptability
Keywords: Lopinavir; ritonavir; pellets; minitabs; acceptability; children